Cold rolled annealed steel sheet and manufacturing method

Through the steel and process treatment of specific chemical components, excellent microstructure is formed, which solves the problems of uneven mechanical properties and insufficient forming capacity of steel plates in the prior art, and achieves steel plate production with high strength, excellent ductility and uniform mechanical properties.

JP7650885B2Active Publication Date: 2025-03-25ARCELORMITTAL SA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022537458
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-12-18
Publication Date
2025-03-25
Estimated Expiration
2039-12-18

AI Technical Summary

Technical Problem

It is difficult to produce cold-rolled hot-rolled steel plates with high strength, excellent ductility and forming capabilities, and their mechanical properties are uneven in the length and width directions.

Method used

Steel materials with specific chemical compositions are used, including 0.060%≦C≦0.085%, 1.8%≦Mn≦2.0%, 0.4%≦Cr≦0.6%, etc., through high-temperature hot rolling, cold rolling and heat treatment processes, 34-80% alkaline with low alkaline carbon content, 10-16% self-warming martensite and 10-50% ferrite in the microstructure, and the surface fraction of non-retrocrystalline iron is controlled to be less than 30%.

Benefits of technology

The high strength, excellent ductility and forming ability of the steel plate are achieved, and the uniformity of mechanical properties in the length and width directions is improved, meeting the needs of automotive structures and safety components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007650885000005
    Figure 0007650885000005
  • Figure 0007650885000006
    Figure 0007650885000006
  • Figure 0007650885000001
    Figure 0007650885000001
Patent Text Reader

Abstract

The steel sheet has a composition comprising 0.060%≦C≦0.085%, 1.8%≦Mn≦2.0%, 0.4%≦Cr≦0.6%, 0.1%≦Si≦0.5%, 0.010%≦Nb≦0.025%, 3.42N≦Ti≦0.035%, 0≦Mo≦0.030%, 0.020%≦Al≦0.060%, 0.0012%≦B≦0.0030%, S≦0.005%, P≦0.050%, 0.002%≦N≦0.007%, and optionally 0.0005%≦Ca≦0.005%, with the remainder being iron and unavoidable impurities. The microstructure consists of 34-80% bainite, 10-16% martensite, and 10-50% ferrite. The surface fraction of non-recrystallized ferrite is less than 30% of the entire structure. The martensite consists of self-tempered martensite and fresh martensite, and the surface fraction of the self-tempered martensite is between 4% and 10%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cold-rolled annealed steel sheet having high strength, excellent ductility and formability, and excellent hole expansion ratio, and also to a method for producing such a cold-rolled annealed steel sheet. [Background technology]

[0002] "Dual phase" steels have been developed to combine high strength and high elongation as a result of a microstructure in which hard martensite or bainite phases are dispersed in a soft ferrite matrix.

[0003] In particular, before forming, these steels have a relatively low yield strength compared to their tensile strength, and as a result, these steels exhibit a very good yield ratio (yield strength / tensile strength ratio) during the forming operation.

[0004] Their strain hardening is very high, which makes it possible to obtain significantly higher yield strengths in the formed parts and better deformation distribution in case of a crash. It is therefore possible to manufacture parts that are as complex as conventional steels, but with higher mechanical properties, so that they meet the same functional specifications as conventional steels, while reducing their thickness. These steels therefore provide an effective response to the lightweight and safety requirements of vehicles.

[0005] In particular, due to their high energy absorption capacity and fatigue strength, the dual phase stainless steels are particularly well adapted for manufacturing structural and safety components of automobiles, such as longitudinal beams, cross members and reinforcements.

[0006] The development of automotive parts with increasingly complex geometries has increased the demand for steels with high tensile strength of at least 780 MPa, as well as very high ductility and formability, especially very high elongation.

[0007] To ensure high ductility and high elongation, a yield strength of at least 350 MPa but not more than 450 MPa before any temper rolling operation (at least 450 MPa and not more than 550 MPa after temper rolling, if performed), a total elongation of at least 15%, and a hole expansion ratio HER of at least 35% are desirable, in addition to a tensile strength of at least 780 MPa and at most 900 MPa.

[0008] The tensile strength TS and total elongation TE are measured according to the ISO standard ISO6892-1 published in October 2009. It must be emphasized that due to differences in the measurement methods, and in particular the geometry of the test specimens used, the values ​​of total elongation TE according to the ISO6892-1 standard are very different from, and in particular lower than, the values ​​of total elongation according to the JIS Z2241 standard.

[0009] In addition, since the yield strength increases due to temper rolling, the yield strength value of a cold-rolled sheet that has not been subjected to any temper rolling cannot be compared with the yield strength value of a steel sheet that has been subjected to temper rolling.

[0010] In this respect, it must be noted that steel sheets that have been subjected to temper rolling are clearly and recognizably different from steel sheets that have not been subjected to temper rolling. Indeed, temper rolling has a clear and well-recognized effect on the surface properties of the sheet, in particular on the work hardening and residual strains at the surface of the sheet. Temper rolling also leaves identifiable and distinctive marks on the surface of the sheet in the form of coarse craters with well-defined shapes. These marks can be easily visualized using an electron microscope.

[0011] The hole expansion ratio HER is measured according to ISO standard 16630:2009. Due to differences in measurement methods, the values ​​of the hole expansion ratio HER according to ISO standard 16630:2009 are very different and not comparable to the values ​​of the hole expansion ratio λ according to JFS T1001 (Japan Iron and Steel Federation standard).

[0012] The hole expansion ratio evaluates the hole flange expansion ability of steel.

[0013] Generally, high hole expansion ratios are associated with high yield ratios (equal to the yield strength divided by the tensile strength) and therefore with high yield strengths for a given tensile strength. In fact, high hole expansion ratios result in particular from small differences in strength between the components of the steel microstructure. However, small differences in strength between the components of the steel microstructure result in high yield ratios.

[0014] As a result, steel sheets having a tensile strength of at least 780 MPa and a high hole expansion ratio generally have a yield strength higher than 450 MPa, even higher than 500 MPa, before any temper rolling, and a yield strength higher than 550 MPa, even higher than 600 MPa, after temper rolling. In contrast, steel sheets having a tensile strength of at least 780 MPa and a yield strength of at most 450 MPa before temper rolling have a low hole expansion ratio.

[0015] It therefore remains desirable to produce cold rolled steel sheets having a tensile strength comprised between 780 MPa and 900 MPa, a yield strength comprised between 350 MPa and 450 MPa before any temper rolling (and between 450 MPa and 550 MPa after temper rolling, if performed), a total elongation of at least 15% and a hole expansion ratio of at least 35%. Summary of the Invention [Problem to be solved by the invention]

[0016] It is therefore an object of the present invention to provide a steel sheet having a tensile strength comprised between 780 MPa and 900 MPa, a yield strength comprised between 350 MPa and 450 MPa before any temper rolling operation (and a yield strength comprised between 450 MPa and 550 MPa after temper rolling, if performed), a total elongation of at least 15% and a hole expansion ratio of at least 35%, and a method for producing same.

[0017] Furthermore, as will be explained in more detail below, the inventors have discovered that adjusting the composition of the steel to obtain these properties is not sufficient, since known manufacturing methods applied to steels having such a designed composition lead to significant inhomogeneities in the mechanical properties in the length and width directions of the plate.

[0018] Preferably, therefore, the present invention further aims to provide a steel sheet having the above mentioned properties such that these properties are uniform throughout the sheet, and a method for producing such a steel sheet.

[0019] Also, in a given production line, the hole expansion ratio generally decreases with increasing sheet thickness. Therefore, the present invention also aims to provide a method for producing cold rolled steel sheet having the above mechanical properties over a wide range of sheet thicknesses from 0.7 mm to 2.3 mm, for example at least 1.5 mm or at least 2.0 mm. [Means for solving the problem]

[0020] For this purpose, the present invention relates to a cold rolled annealed steel sheet having the following properties in weight percent: 0.060%≦C≦0.085% 1.8%≦Mn≦2.0% 0.4%≦Cr≦0.6% 0.1%≦Si≦0.5% 0.010%≦Nb≦0.025% 3.42N≦Ti≦0.035% 0≦Mo≦0.030% 0.020%≦Al≦0.060% 0.0012%≦B≦0.0030% S≦0.005% P≦0.050% 0.002%≦N≦0.007% and optionally 0.0005%≦Ca≦0.005% and preferably consisting of these, with the remainder being iron and inevitable impurities resulting from refining, and the cold-rolled annealed steel sheet has a surface fraction of the following: - between 34 and 80% bainite, - between 10 and 16% martensite, and - A microstructure consisting of 10-50% ferrite, in which the surface fraction of non-recrystallized ferrite with respect to the entire structure is less than 30%, The present invention relates to a cold-rolled annealed steel sheet in which the martensite is composed of self-tempered martensite and fresh martensite, and the surface fraction of the self-tempered martensite is between 4% and 10% with respect to the entire structure.

[0021] Preferably, the bainite is low carbide content bainite and has a grain size of 100 μm or less. 2 Contains less than 100 carbides per surface unit.

[0022] In an embodiment, the cold rolled annealed steel sheet is not temper rolled, and the cold rolled annealed steel sheet has a tensile strength TS comprised between 780 MPa and 900 MPa, a yield strength YS comprised between 350 MPa and 450 MPa, a total elongation TE of at least 15%, and a hole expansion ratio HER of at least 35%, measured according to ISO standard 16630:2009.

[0023] In another embodiment, the cold rolled annealed steel sheet is a temper rolled sheet having a tensile strength TS comprised between 780 MPa and 900 MPa, a yield strength YS comprised between 450 MPa and 550 MPa, a total elongation TE of at least 15%, and a hole expansion ratio HER of at least 35%, measured according to ISO standard 16630:2009.

[0024] Generally, cold rolled steel sheets and annealed steel sheets have a thickness comprised between 0.7 mm and 2.3 mm, for example at least 2.0 mm.

[0025] Preferably, the cold rolled annealed steel sheet has a length in the rolling direction of at least 500 m, and the difference in tensile strength between the highest tensile strength region and the lowest tensile strength region of the cold rolled annealed steel sheet is at most 7% of the tensile strength of the highest tensile strength region.

[0026] According to an embodiment, the cold rolled annealed steel sheet comprises a coating of zinc or a zinc alloy obtained by continuous dip coating.

[0027] In another embodiment, the cold rolled annealed steel sheet comprises a zinc or zinc alloy coating obtained by vacuum deposition.

[0028] The present invention also relates to a method for manufacturing a cold rolled annealed steel sheet, comprising the following successive steps: The following, in percent by weight: 0.060%≦C≦0.085% 1.8%≦Mn≦2.0% 0.4%≦Cr≦0.6% 0.1%≦Si≦0.5% 0.010%≦Nb≦0.025% 3.42N≦Ti≦0.035% 0≦Mo≦0.030% 0.020%≦Al≦0.060% 0.0012%≦B≦0.0030% S≦0.005% P≦0.050% 0.002%≦N≦0.007% and optionally 0.0005%≦Ca≦0.005% providing a semi-finished product made of steel having a composition comprising, and preferably consisting of, the remainder of the composition being iron and inevitable impurities resulting from smelting, - The semi-finished product is heated to a temperature T of 1200°C or higher. H1 Then, the heated semi-finished product is heated to 3000° C. NR The final rolling temperature T FRT (Ar3 is the temperature at which the austenite transformation begins when the steel is cooled, and T NR is the non-recrystallization temperature of steel), a process for obtaining a hot-rolled steel sheet; The hot-rolled steel sheet is cooled at a first cooling rate of at least 10 ° C / s to a coiling temperature T higher than the martensite finish temperature Mf of the steel and lower than 500 ° C. coil and the hot-rolled steel sheet is cooled to a coiling temperature Tcoil to obtain a structure consisting of bainite, optionally martensite and / or pearlite, the surface fraction of pearlite being less than 15%; - cold rolling the hot rolled steel sheet at a cold rolling reduction of at least 40% to obtain a cold rolled steel sheet; The cold-rolled steel sheet is annealed at an annealing temperature T between Ac3-20°C and Ac3+15°C. H2 reheating to an annealing temperature T H2 The average heating temperature V between 1℃ / sec and 50℃ / sec H and the average heating rate V between 600°C and Ac1, between 1°C / s and 10°C / s H’ The cold-rolled steel sheet is then reheated at the annealing temperature T H2 Annealing time t for at least 30 seconds H2 to obtain a structure containing at least 50% austenite; The cold-rolled steel sheet is cooled at a second cooling rate V between 10 ° C / sec and 50 ° C / sec. C2 Temperature T is between 440℃ and 480℃ C cooling until The cold-rolled steel sheet is held at a temperature in the range of 440°C to 480°C for a holding time t in the range of 20 seconds to 500 seconds. C holding for a period of - cooling the cold rolled steel sheet at a third cooling rate of at least 1°C / s to ambient temperature.

[0029] Preferably, the annealing time t H2 is a maximum of 500 seconds.

[0030] In the embodiment, the annealing time t H2 is included between Ac3 and Ac3+15℃, and the second cooling rate V C2 is between 10°C / sec and 20°C / sec.

[0031] Generally, the surface fraction of cold rolled annealed steel sheet is as follows: - between 34 and 80% bainite, - between 10 and 16% martensite, and - A microstructure consisting of 10-50% ferrite, in which the surface fraction of non-recrystallized ferrite with respect to the entire structure is less than 30%, The martensite is composed of self-tempered martensite and fresh martensite, and the surface fraction of the self-tempered martensite is between 4% and 10% with respect to the entire structure.

[0032] In an embodiment, during said holding in the temperature range comprised between 440°C and 480°C, the cold rolled steel sheet is hot-dip galvanized in a bath having a temperature of 480°C or less.

[0033] Preferably, the cold rolled annealed steel sheet is coated with Zn or a Zn alloy.

[0034] In another embodiment, after cooling to ambient temperature, the zinc or zinc alloy coating is applied by vacuum deposition.

[0035] Preferably, the cold rolling reduction is between 40% and 80%.

[0036] In an embodiment, after cooling to ambient temperature, the steel sheet is temper rolled with a temper reduction comprised between 0.1 and 0.4%.

[0037] The invention will now be described in detail with reference to the accompanying drawings, in which: FIG. [Brief description of the drawings]

[0038] [Figure 1] 1 is a photomicrograph showing the structure of a steel sheet not according to the present invention. [Diagram 2] 1 is a micrograph showing the structure of a steel sheet according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0039] In this application, Ac1 denotes the onset of the allotropic transformation temperature upon heating.

[0040] Ac1 can be measured by dilatometry or evaluated by the following formula published in "Darstellung der Umwandlungen für technische Anwendungen und Moeglichkeiten ihrer Beeinflussung", HP Hougardy, Werkstoffkunde Stahl Band 1, 198-231, Verlag Stahleisen, Duesseldorf, 1984: Ac1=739-22*C-7*Mn+2*Si+14*Cr+13*Mo-13*Ni

[0041] In this formula, Ac1 is expressed in degrees Celsius, and C, Mn, Si, Cr, Mo and Ni are the contents of C, Mn, Si, Cr, Mo and Ni in the composition expressed as weight percent.

[0042] Furthermore, Ar3 indicates the austenite transformation start temperature during cooling, and T NR indicates the non-recrystallization temperature of the steel, and Ac3 indicates the austenite transformation finish temperature when heated.

[0043] The temperatures Ar3 and Ac3 can be measured by dilatometry or evaluated with the Thermo-Calc® software known per se. The non-recrystallization temperature T NR can be measured.

[0044] Furthermore, Mf denotes the martensite finish temperature, i.e. the temperature at which the transformation from austenite to martensite is completed upon cooling. Mf can be measured by dilatometry.

[0045] Hereinafter, the contents of the elements of the chemical composition of the steel are given in % by weight (or parts per million, i.e. ppm).

[0046] In the chemical composition of steel, carbon plays a role in the formation of the microstructure and the mechanical properties.

[0047] To ensure a tensile strength of at least 780 MPa, a yield strength comprised between 350 MPa and 450 MPa before any temper rolling (and between 450 MPa and 550 MPa after temper rolling) and a hole expansion ratio of at least 35%, the carbon content is comprised between 0.060% and 0.085%. If the C content is lower than 0.060%, the tensile strength does not reach 780 MPa. If the C content is higher than 0.085%, too much pearlite is formed during coiling, resulting in a banded structure, which has a negative effect on the hole expansion ratio. Also, if the bainite contains too much carbide, the yield strength may exceed 450 MPa (before temper rolling) and the total elongation may not reach 15%. Preferably, the C content is less than or equal to 0.075%.

[0048] To obtain a microstructure containing at least 10% martensite and having a tensile strength of at least 780 MPa, at least 1.8% manganese and at least 0.4% chromium are added to increase the hardenability of the steel.

[0049] In particular, to obtain sufficient hardenability, the Mn content is at least 1.8%. However, if the Mn content is higher than 2.0%, the stabilization of austenite is too strong and the Ms temperature is too high, resulting in too high a martensite fraction upon cooling from the annealing temperature. As a result, the yield strength exceeds 450 MPa (before temper rolling). Also, a Mn content higher than 2.0% leads to a banded structure, which is detrimental to the hole expansion ratio. As a result, the hole expansion ratio does not reach 35%.

[0050] Unlike manganese, chromium does not affect the proportion of austenite during annealing. Therefore, chromium is added in addition to Mn to further increase the hardenability of the steel, and a Cr content of at least 0.4% together with a Mn content of at least 1.8% provides sufficient hardenability to obtain a tensile strength of at least 780 MPa. In fact, below 0.4%, a too high ferrite fraction may be obtained while the fraction of self-tempered martensite is insufficient. Above 0.6% Cr, the coatability of the steel decreases and the cost of the addition is excessive. Therefore, the Cr content is at most 0.6%.

[0051] At a content of at least 0.1%, silicon provides hardening of the ferrite, thus reducing the hardness difference between the microstructural constituents and increasing the hole expansion ratio. Silicon has a low carbide content, i.e., below 100 μm 2 It favors the formation of bainite containing less than 100 carbides per surface unit of the steel. However, excess Si reduces the coverage by promoting the formation of oxides that adhere to the surface of the sheet and leads to too strong stabilization of ferrite. Therefore, the Si content is maximum 0.5%.

[0052] Titanium and niobium are micro-alloying elements used together according to the invention to provide precipitation hardening and to make it possible to achieve a tensile strength of at least 780 MPa while limiting the martensite fraction to a maximum of 16%.

[0053] At contents of 3.42*N~0.035% (N is the N content in the steel in % by weight), titanium mainly combines with nitrogen and carbon, precipitating in the form of fine nitrides and / or carbonitrides, making it possible to control the austenite grain size. Titanium also has a positive effect on the weldability of the steel. If the titanium content exceeds 0.035%, there is a risk of forming coarse titanium nitrides which precipitate from the liquid state, which tend to reduce the ductility and lead to premature damage during hole expansion tests and therefore reduce the hole expansion ratio.

[0054] At this content, titanium ensures that the nitrogen is completely bound in the form of nitrides or carbonitrides, so that the boron is free and can play an effective role in hardenability.

[0055] At a content of at least 0.010%, niobium is very effective in forming fine niobium carbonitrides during annealing in the temperature range near the critical transformation range, resulting in precipitation hardening. In addition, Nb refines the austenite grains, thus further limiting the pearlite fraction in the hot-rolled sheet for coiling. If the Nb content is less than 0.010%, the austenite grain size becomes too large and the final structure contains too much self-tempered martensite. As a result, the yield strength becomes too high. However, if it exceeds 0.025%, niobium excessively retards the recrystallization of ferrite during annealing, resulting in a structure containing more than 30% non-recrystallized ferrite, which can no longer achieve the targeted hole expansion ratio.

[0056] At least 0.0012% boron is added to limit the activity of carbon, control and limit the diffusion phase transformation (pearlite transformation during cooling), and form the hardening phases (bainite or martensite) required to obtain the desired tensile strength. The addition of B also limits the addition of hardening elements such as Mn, Mo, Cr, and allows for a lower cost steel grade. However, above 0.0030%, B may co-segregate with C, leading to the formation of a banded structure, which is detrimental to the hole expansion ratio. Therefore, the B content is at most 0.0030%. Preferably, the B content is at least 0.0015% and / or at most 0.0025%.

[0057] The composition may contain a maximum of 0.030% molybdenum as a residual element. If present at a content higher than 0.030%, Mo may retard the precipitation of Nb and Ti during annealing, retard recrystallization and cause excessive refinement of the ferrite grains.

[0058] Aluminum is a very effective element for deoxidizing steel in the liquid phase during refining. To obtain sufficient deoxidization of the steel, the Al content is at least 0.020%. However, the Al content must be at most 0.060% to avoid an increase in the temperature Ac3 and to be able to control the formation of ferrite during cooling.

[0059] A minimum nitrogen content of 0.002% is required to form sufficient amounts of nitrides and carbonitrides. The nitrogen content is limited to 0.007% to prevent the formation of coarse TiN precipitates from the liquid state, which reduces ductility and tends to lead to premature failure during hole expansion testing, reducing the hole expansion ratio.

[0060] Optionally, the steel can undergo a treatment for spheroidization of sulfides carried out with calcium, which has the effect of improving the hole expansion ratio due to MnS spheroidization. The composition of the steel can therefore contain at least 0.0005% and at most 0.005% Ca.

[0061] The balance of the steel composition is iron and impurities resulting from smelting. In this respect, nickel, copper, sulfur and phosphorus are considered as residual elements that are unavoidable impurities. Their contents are therefore max. 0.05% Ni, max. 0.03% Cu, max. 0.005% S and max. 0.050% P.

[0062] If the sulfur content exceeds 0.005%, the presence of excess sulfides such as MnS reduces the ductility, especially the hole expansion ratio. Achieving a very low S content, i.e., less than 0.0001%, is very costly and offers no benefit. Therefore, the S content is generally 0.0001% or more.

[0063] However, the present invention reduces the sensitivity of the hole expansion ratio to the S content of the steel, so that a hole expansion ratio of at least 35% is obtained even with S contents of more than 0.001%, which are less expensive to obtain. Thus, according to an embodiment, the S content is at least 0.001%.

[0064] Phosphorus is an element that reduces spot weldability and hot ductility, especially due to its tendency to segregate at grain boundaries and co-segregate with manganese. For these reasons, its content must be limited to a maximum of 0.050%, preferably to a maximum of 0.015%. However, it is very expensive to achieve very low P contents, i.e., P contents lower than 0.001%, so the P content is generally 0.001% or higher.

[0065] The microstructure of the cold rolled annealed steel sheet according to the present invention is composed of, in terms of surface fraction, 34% to 80% bainite, 10% to 16% martensite, and 10% to 50% ferrite.

[0066] A ferrite fraction of at least 10% contributes to achieving a total elongation of at least 15%.

[0067] The ferrite may consist of intercritical ferrite, as described below, or may include intercritical ferrite and ferrite formed upon cooling during annealing of the cold rolled steel sheet as described below. The ferrite formed upon cooling is hereinafter referred to as "transformed ferrite". In particular, the annealing temperature T H2 However, as described above, when the annealing temperature T is lower than Ac3, that is, when the annealing temperature T is between Ac3-20°C and Ac3, the ferrite contains transformation interval ferrite and can further contain transformed ferrite. H2 If Ac3 is lower than Ac3, the ferrite consists of intercritical ferrite or of intercritical and transformed ferrite.

[0068] In contrast, the annealing temperature T H2 If Ac3 or more, the ferrite consists of converted ferrite.

[0069] "Transformed ferrite" is different from the intercritical ferrite remaining in the structure at the end of the annealing process. In particular, transformed ferrite is rich in manganese, i.e. has a manganese content higher than the average manganese content of the steel and higher than that of intercritical ferrite. Intercritical and transformed ferrite can therefore be differentiated by observing micrographs in a FEG-TEM microscope with secondary electrons after etching with metabisulfate. On the micrograph, intercritical ferrite appears medium grey, whereas transformed ferrite appears dark grey due to its higher manganese content.

[0070] Some of the ferrite may not be recrystallized. In other words, the ferrite may contain non-recrystallized ferrite. However, the structure must contain less than 30% (by surface fraction) non-recrystallized ferrite. This percentage is expressed with reference to the entire structure.

[0071] Having less than 30% non-recrystallized ferrite is important to achieve the targeted mechanical properties, in particular a hole expansion ratio of at least 35%. Indeed, if the structure contains more than 30% non-recrystallized ferrite, a banded structure is achieved, so that the hole expansion ratio does not reach 35%.

[0072] Preferably, the surface fraction of non-recrystallized ferrite is at most 25%, more preferably at most 20%.

[0073] Martensite results from the diffusionless transformation of austenite below the Ms temperature on cooling. Martensite is generally in the form of islands.

[0074] A martensite fraction of at least 10% is necessary to obtain a tensile strength of at least 780 MPa. However, due to the high yield strength of martensite, a martensite fraction higher than 16% would result in a yield strength higher than 450 MPa before temper rolling and higher than 550 MPa after temper rolling. Furthermore, a martensite fraction higher than 16% would worsen the hole expansion ratio. Therefore, the martensite fraction is a maximum of 16%.

[0075] The martensite consists of self-tempered martensite and optionally fresh martensite (i.e., neither tempered nor self-tempered).

[0076] The surface fraction of the self-tempered martensite is comprised between 4% and 10% relative to the overall structure. In particular, a surface fraction of the self-tempered martensite higher than 10% will result in a yield strength higher than 450 MPa before temper rolling (and higher than 550 MPa after temper rolling, if performed).

[0077] Furthermore, having 10-16% martensite and a surface fraction of self-tempered martensite comprised between 4% and 10% contributes to achieving a yield strength of at least 350 MPa and up to 450 MPa and a hole expansion ratio HER of at least 35% before any temper rolling.

[0078] For self-tempered martensite, this definition refers to that given in "Les principes de base de traitement thermique des aciers" by A. Constant and G. Henry, PYC 1986, p. 157.

[0079] Martensite generally has a C content below 0.75%.

[0080] A bainite fraction of at least 34% contributes to achieving a yield strength comprised between 350 MPa and 450 MPa before temper rolling and a hole expansion ratio of at least 35%. In fact, the yield strength of bainite is lower than that of martensite. Furthermore, the difference in hardness between bainite and ferrite is small, and bainite contributes to avoiding the formation of a striped structure by separating island martensite and improving the hole expansion ratio.

[0081] If the bainite fraction is higher than 80%, the structure does not contain at least 10% martensite and at least 10% ferrite and the tensile strength or total elongation becomes too low.

[0082] Bainite forms during cooling from the fully austenitic or intercritical temperature range above the Ms temperature. Bainite takes the form of aggregates of bainite laths and cementite particles. Its formation involves short-range diffusion.

[0083] In the following, a distinction will be made between carbide-containing bainite and low-carbide-containing bainite.

[0084] Low carbide content bainite is 100 μm 2 It refers to bainite containing less than 100 carbides per surface unit of steel. During cooling, low carbide content bainite forms between 550 and 450 °C.

[0085] Unlike low carbide content bainite, carbide-containing bainite always contains more than 100 carbides per 100 square micrometer surface units.

[0086] Preferably, the bainite in the structure is constituted by low carbide content bainite. Having only low carbide content bainite contributes to achieving a yield strength of up to 450 MPa and a total elongation of at least 15% before temper rolling.

[0087] The plate structure does not contain any austenite.

[0088] These microstructural features are determined by observing the microstructure, for example using a scanning electron microscope with a field effect barrel ("SEM-FEB" technique) at a magnification of more than 1200 times, in combination with an EBSD ("electron backscatter diffraction") detector, followed by determining the morphology of the laths and grains by image analysis using programs known per se, for example the Aphelion® program.

[0089] The fraction of non-recrystallized ferrite is determined by observing the microstructure with a scanning electron microscope after chemical polishing with a solution composed of hydrofluoric acid and hydrogen peroxide.

[0090] Cold rolled annealed steel sheets generally contain fine titanium carbonitrides and / or niobium carbonitrides. In particular, the surface density of these carbonitrides, which have a maximum dimension of less than 5 nm, is 10 4 / μm 2 Here, the maximum dimension of the carbonitride refers to the maximum ferret diameter of the carbonitride.

[0091] This surface density can be measured by observing a sample with a transmission electron microscope (TEM).

[0092] This cold-rolled annealed steel sheet is produced, for example, by a method including the following successive steps.

[0093] The steel having the composition as described above is cast to obtain a semi-finished steel product. The steel may be cast to obtain an ingot or may be continuously cast in the form of a slab with a thickness of about 200 mm. At this stage, the semi-finished product contains (TiNb)(CN) precipitates.

[0094] The steel semi-finished products are subjected to a temperature T of at least 1200 ° C so that they reach at all points a temperature favorable for the large deformations that the steel undergoes during rolling. H1 During heating, the (TiNb)(CN) precipitates dissolve.

[0095] This semi-finished product is hot-rolled in a temperature range in which the structure of the steel becomes completely austenitic, and the final rolling temperature T FRT is temperature Ar3 ~ non-recrystallization temperature T NR and a hot rolled steel sheet is obtained.

[0096] T FRT If Ar is lower than Ar3, ferrite grains will form below Ar3 before the end of rolling. These grains will strain harden during rolling, reducing ductility.

[0097] T FRT T NR If the temperature is higher than 100°C, the iron borocarbide Fe 23 (BC)6 precipitates at the grain boundaries, thereby hindering the hardening effect of B. In fact, these precipitates will not dissolve in the subsequent steps of the manufacturing process.

[0098] Generally, the final rolling temperature T FRT is between 850℃ and 930℃.

[0099] During hot rolling, fine titanium nitride particles are generally precipitated, the maximum dimensions of which are generally comprised between 150 nm and 200 nm.

[0100] The rolled steel product is then subjected to a first cooling rate V of at least 10 ° C / s. C1 At a coiling temperature T lower than 500°C coil Cool to room temperature and roll up.

[0101] In order to avoid the transformation of austenite into ferrite and pearlite during cooling and to avoid partial niobium precipitation, the first cooling rate V C1 is at least 10° C. / sec.

[0102] Winding temperature T coil must be lower than 500°C and higher than the martensite finish temperature Mf.

[0103] In fact, the inventors have found that the winding temperature T coilThey found that when the temperature was above 500°C, the mechanical properties of the plate were non-uniform along the length and width, and the tensile strength did not reach 780 MPa, and was even lower than 600 MPa in at least some parts of the plate.

[0104] The inventors have investigated this phenomenon and found that it is largely due to the low Mn content in the steel required to obtain a maximum yield strength of 450 MPa and a hole expansion ratio of at least 35% before temper rolling.

[0105] In particular, Mn generally retards the transformation of austenite to bainite and / or martensite during coiling, especially for steels with Mn contents higher than 2.0%, which do not require yield strengths of up to 450 MPa before temper rolling or up to 550 MPa after temper rolling, and / or have low hole expansion ratios.

[0106] Decreasing the Mn content up to 2.0% accelerates the transformation of austenite to bainite during coiling, leading to an increase in temperature in the coiled sheet, especially in the center and axial regions of the coil.

[0107] The coil center is defined as the portion of the plate extending along the length of the plate from a first end located at 30% of the total length of the plate to a second end located at 70% of the total length of the plate, and the axial region is defined as the region centered about the longitudinal central axis of the plate and having a width equal to 60% of the total width of the plate.

[0108] In the center and axial regions, the windings are continuous and therefore cannot dissipate the heat generated by the transformation of austenite to bainite to a significant extent.

[0109] If the coiling temperature is above 500°C, this temperature increase leads to the precipitation of borocarbides and coarse titanium and niobium carbides, thereby inhibiting the precipitation hardening potential of B, Ti and Nb. Moreover, the effect of Nb on recrystallization refinement is hindered, resulting in too coarse ferrite grains. Furthermore, this temperature increase leads to the coalescence of cementite. In particular, the cementite is not completely dissolved, so that too little C is available for austenite. Thus, too little austenite is formed in the region located in the center and axial region of the coil during coiling, leading to too low a martensite fraction in this region in the final microstructure. As a result of these two effects, the tensile strength does not reach 780 MPa in this region of the plate.

[0110] Furthermore, if the coiling temperature is above 500° C., the mechanical properties of the sheet are not uniform in either the length or width direction of the sheet.

[0111] The inventors have found that when coiling is performed at temperatures below 500° C., despite the increase in temperature due to the transformation of austenite to bainite, there is no coalescence of cementite, and no precipitation of borocarbides or coarse titanium and niobium carbides occurs, therefore the tensile strength does not decrease and the mechanical properties of the plate are uniform along the length and width of the plate.

[0112] Coiling at temperatures below 500° C. also makes it possible to limit the fraction of pearlite formed during coiling, thereby avoiding the formation of banding that is detrimental to the hole expansion ratio in the subsequent steps of the process.

[0113] However, if the coiling temperature is below Mf, it becomes too difficult to cold roll the steel.

[0114] Preferably, the coiling temperature is at least 300°C, more preferably at least 350°C or at least 400°C.

[0115] During coiling, the austenite transforms into bainite and, optionally, martensite and / or pearlite, so that at the end of coiling, the structure of the entire sheet consists of bainite and, optionally, martensite and / or pearlite (the surface fraction of pearlite is less than 15%) and is free of ferrite. In particular, the structure is uniform along the length and width of the sheet. The bainite has a low carbide content, i.e., less than 100 μm. 2 bainite containing less than 100 carbides per surface unit.

[0116] At this stage the plate contains B, Nb and Ti in solid solution, in particular the Nb content in solid solution is at least 0.01%.

[0117] This microstructure of the hot rolled sheet after coiling is important to obtain the desired mechanical properties. Indeed, the kinetics of recrystallization during the subsequent annealing process, which depends on the microstructure of the hot rolled sheet after coiling, has a significant effect on the structure formed during annealing, especially on the size and shape of the austenite grains. In particular, when the sheet structure after coiling contains 15% or more pearlite, austenite mainly nucleates and grows during annealing in the areas of the sheet containing pearlite, leading to a banded structure.

[0118] Next, the hot-rolled steel sheet is cold-rolled at a cold-rolling reduction of at least 40% to obtain a cold-rolled steel sheet. If the reduction is less than 40%, the strain imparted to the structure is insufficient, and recrystallization during the subsequent annealing becomes insufficient, resulting in a striped structure.

[0119] The cold rolling reduction is generally between 40 and 80%.

[0120] Cold-rolled steel sheets generally have a thickness comprised between 0.7 mm and 2.3 mm, for example at least 1.5 mm or at least 2.0 mm.

[0121] Next, the cold-rolled steel sheet is annealed at an annealing temperature T between Ac3-20℃ and Ac3+15℃. H2 Reheat until cooked through.

[0122] Annealing temperature T H2 Average heating rate V up to H is between 1 °C / s and 50 °C / s. Furthermore, the average heating rate V between 600 °C and Ac1 is H’ is between 1°C / sec and 10°C / sec.

[0123] Average heating rate V between 600℃ and Ac1 H is different from the average heating rate between the start of the heat treatment (e.g., room temperature) and Ac1, and the annealing temperature T H2 Average heating rate V up to H It should be noted that it is different.

[0124] Average heating rate V H and V H’ is achieved, for example, by heating the cold-rolled sheet in a continuous annealing furnace having several zones through which the sheet moves. In each of these zones of the furnace, the furnace settings (e.g. temperature in the zone, heating power, etc.) are controlled to achieve a specific target heating rate in this zone. This control results in an average heating rate V to the annealing temperature, which is comprised between 1 °C / s and 50 °C / s. H , and the average heating rate V between 600°C and Ac1, which is between 1°C / s and 10°C / s H’ It is possible to achieve this.

[0125] During heating between 600°C and Ac1, recrystallization occurs and fine titanium and niobium carbonitrides precipitate in the steel. Having fine precipitates makes it possible to still have enough Nb in solid solution to control the size of the ferrite grains during recrystallization by avoiding too significant growth of the ferrite grains.

[0126] The inventors measured the average heating rate V between 600 °C and Ac1. H’ Controlling the heating time between 600 °C and Ac1, which corresponds to the time from the start of recrystallization to the end of recrystallization, is important for the kinetics of the latter phase transformation, especially the annealing temperature T H2 We found that this was important for the kinetic kinetics during the subsequent retention phase at .

[0127] In particular, control of the average heating rate between 600°C and Ac1 allows control of the size and aspect ratio of the ferrite grains obtained at Ac1. During the subsequent heating from Ac1 to the annealing temperature, the austenite grains are nucleated at the grain boundaries of the recrystallized ferrite. Thus, control of the average heating rate between 600°C and Ac1 allows control of the austenite grain size and carbon re-enrichment at the end of the annealing, as well as the final microstructure.

[0128] Average heating rate V less than 1°C / sec H’ would result in an excessively long heating time between 600°C and Ac1 and thus excessive growth of the ferrite grains and the subsequently formed austenite grains. Excessive size of the austenite grains would lead to the formation of an excessively high fraction of martensite during the further steps of the manufacturing process, in particular an excessively high fraction of self-tempered martensite in the final structure, resulting in a too high yield strength.

[0129] Conversely, average heating rates V higher than 10 °C / s H’ would result in insufficient or no recrystallization of ferrite during heating from 600°C to Ac1. As a result, austenite nucleates in the carbon-rich regions, i.e., in bands of pearlite and martensite, resulting in a banded final structure, which is detrimental to the hole expansion ratio.

[0130] The average heating rate V between 600°C and Ac1, between 1°C / s and 10°C / s H’ makes it possible to obtain, at the end of said manufacturing method, a steel whose microstructure consists, in surface fractions, of between 34% and 80% bainite, between 10% and 16% martensite and between 10% and 50% ferrite, with a proportion of self-tempered martensite comprised between 4% and 10%, such that the surface fraction of non-recrystallized ferrite in the structure is less than 30%.

[0131] Annealing temperature T H2is included in the range of Ac3-20℃ to Ac3+15℃, and the annealing temperature T H2 At the end of the hold at 0° C., a structure is obtained which consists of at least 50% austenite and optionally ferrite.

[0132] Annealing temperature T H2 If Ac is lower than Ac3-20°C, the structure may contain too much ferrite and / or not enough bainite and / or self-tempered martensite, and the hole expansion ratio HER does not reach 35%.

[0133] Annealing temperature T H2 If Ac3+15°C is higher, the austenite grain size is too large. This excessive austenite grain size leads to the formation of too high a fraction of bainite and too high a fraction of self-tempered martensite in the final structure, while an insufficient fraction of ferrite forms on cooling. As a result, the yield strength is too high and the total elongation is too low.

[0134] Annealing temperature T of the plate H2 for an annealing time t of at least 30 seconds, preferably up to 500 seconds. H2 This annealing temperature T H2 During holding at RT, the austenite grains grow followed by precipitation of titanium carbonitride and niobium carbonitride.

[0135] Annealing time t H2 If the annealing time t is shorter than 30 seconds, the austenite grains are too small. As a result, the final structure contains an insufficient martensite fraction and an excessive ferrite fraction, and a tensile strength of at least 780 MPa is not achieved. H2 If the time is longer than 500 seconds, the niobium and titanium precipitates may coalesce, thereby inhibiting the hardening effect of Nb and Ti, and the austenite grains may be too large, resulting in a yield strength of more than 450 MPa, not a tensile strength of at least 780 MPa, and / or a hole expansion ratio of less than 35%.

[0136] Then, a second cooling rate V is applied between 10 ° C / s and 50 ° C / s. C2 The plate is heated to a temperature T between 440℃ and 480℃. C During this cooling step, the austenite is partially transformed into bainite and optionally ferrite.

[0137] This cooling occurs at a temperature T H2 from the first step to the second step, which in the latter case may involve different cooling modes such as cold or boiling water bath, water jets or gas jets.

[0138] The second cooling rate V C2 If the melting rate is lower than 10° C. / s, the final structure contains an excessive ferrite fraction and an insufficient martensite and / or bainite fraction, and the tensile strength does not reach 780 MPa and the hole expansion ratio does not reach 35%.

[0139] If the annealing temperature is between Ac3 and Ac3+15°C, the second cooling rate V is used to transform part of the austenite into ferrite so that the final structure contains at least 10% ferrite. C2 is preferably at most 20° C. / sec.

[0140] Next, the steel sheet is subjected to a temperature range of 440 to 480°C for a holding time t C Hold for .

[0141] At this stage, partial transformation of retained austenite to bainite occurs. Holding time t C If the holding time t is shorter than 20 seconds, an insufficient fraction of bainite will be formed. C If the time is longer than 500 seconds, the bainite fraction is too large and the martensite fraction in the final structure is insufficient.

[0142] Preferably, the retention time t C is a maximum of 50 seconds.

[0143] Optionally, the steel sheet is hot-dip galvanized in a zinc or zinc alloy bath at a temperature TZn lower than 480°C during the hold in the temperature range comprised between 440°C and 480°C.

[0144] Optionally, immediately after leaving the zinc or zinc alloy bath after galvanizing, for a time t generally comprised between 10 and 40 seconds G Temperature T between 490 and 550°C G The steel sheet can be galvanized by heating to a temperature of 1000.degree.

[0145] Immediately after holding in the temperature range between 440 ° C. and 480 ° C., or immediately after galvanizing or galvannealed hot-dip galvanizing, if performed, a third cooling rate V of at least 1 ° C. / s C3 The plate is cooled to ambient temperature at 1000 K. During this cooling process, the retained austenite transforms to fresh martensite and / or bainite.

[0146] This manufacturing method provides a cold-rolled annealed steel sheet, the structure of which is composed of 34% to 80% bainite, 10% to 16% martensite, and 10% to 50% ferrite in terms of surface fraction. The surface fraction of non-recrystallized ferrite in the structure is less than 30%. The martensite is composed of self-tempered martensite and fresh martensite, and the surface fraction of the self-tempered martensite is comprised between 4% and 10% of the total structure.

[0147] After cooling to room temperature, if no galvanizing has been carried out, the cold-rolled annealed steel sheet may be coated by vacuum deposition, for example by physical vapor deposition (PVD) or jet vapor deposition (JVD) type.

[0148] The inventors have shown that the cold rolled annealed steel sheet produced by this manufacturing method has a tensile strength comprised between 780 and 900 MPa, a yield strength comprised between 350 and 450 MPa, a total elongation of at least 15%, or even at least 18%, and a hole expansion ratio HER of at least 35%.

[0149] A yield strength between 350 and 450 MPa is achieved immediately after cooling to room temperature without temper rolling.

[0150] In particular, the addition of niobium and titanium in the composition and the precipitation of fine niobium and titanium carbonitrides during the annealing process make it possible to obtain a tensile strength of 780 MPa with a relatively low martensite fraction of up to 16%. The yield strength therefore remains at a maximum of 450 MPa and the hole expansion ratio can exceed 35% as the hardness difference between the microstructural components is reduced.

[0151] Optionally, after cooling to room temperature, temper rolling is performed, in which case the cold-rolled annealed steel sheet has a tensile strength comprised between 780 and 900 MPa, a yield strength comprised between 450 and 550 MPa, a total elongation of at least 15%, or even 18%, and a hole expansion ratio HER of at least 35%.

[0152] For example, temper rolling is carried out with a reduction comprised between 0.1% and 0.4%, for example between 0.1% and 0.2%.

[0153] Moreover, these mechanical properties are achieved over a wide range of thicknesses of cold rolled annealed steel sheet, ranging from 0.7 mm to 2.3 mm. These properties are particularly achieved when the sheet thickness is at least 2.0 mm and up to 2.3 mm.

[0154] Furthermore, the mechanical properties, especially the tensile strength, are uniform across the length and width of the plate. In particular, considering a full cold rolled annealed steel plate with a length in the rolling direction of at least 500 m, the difference in tensile strength between the highest tensile strength region and the lowest tensile strength region of the cold rolled annealed steel plate is at most 7% of the tensile strength of the highest tensile strength region. EXAMPLES

[0155] As examples and comparisons, plates are manufactured made of steel compositions according to Table I, the elements being expressed in % by weight or ppm (parts per million).

[0156] [Table 1]

[0157] In this table, "res" means that the corresponding element is present as a residual whose content is lower than the lower range defined for this element. In particular, a residual amount of Ti means that the Ti content is less than 3.42N, a residual amount of B means that the B content is less than 0.0012%, etc. The underlined values ​​are not according to the invention.

[0158] The values ​​of the transformation Ac3 are also reported in Table I. Ac3 was evaluated with Thermo-Calc® software.

[0159] Steels having the compositions disclosed in Table I were cast to obtain ingots. These ingots were heated at a temperature T H1 and then hot-rolled at a final rolling temperature T FRT Ar3~T NR The hot rolled steel sheet was obtained.

[0160] The hot-rolled steel sheet is cooled at a first cooling rate V of 30 °C / s. C1 The winding temperature T coil Cool to this temperature T coil The coiling temperature was above Mf for all the examples and comparative examples, resulting in a structure consisting of bainite and optionally martensite and / or pearlite, with the surface fraction of pearlite being less than 15%.

[0161] Thereafter, the hot-rolled steel was pickled and cold-rolled at a rolling reduction of 50% to obtain a cold-rolled sheet having a thickness of 1.4 mm.

[0162] The cold-rolled sheet is heated at an average heating rate V H At annealing temperature T H2 The average heating rate between 600℃ and Ac1 was V H’ At annealing temperature T H2 Reheat for annealing time t H2 Annealing temperature T H2 maintained.

[0163] The plate is then cooled at a second cooling rate V C2 At temperature T C Cool to 30°C and hold for t C The sheet is then galvanized by hot-dip galvanization in a zinc bath at a temperature of up to 480° C. and cooled at a third cooling rate V of at least 1° C. / s. C3 The mixture was cooled to room temperature.

[0164] The sheets were finally temper rolled with temper reductions ranging between 0.1 and 0.4%.

[0165] The treatment conditions are reported in Table II.

[0166] [Table 2]

[0167] In Table II, the underlined values ​​are not in accordance with the present invention. H2 The value of is such that the structure as annealed contains at least 50% austenite.

[0168] The microstructure of the steel sheets thus obtained was determined. After etching with sodium bisulfite, the surface fraction of martensite (including tempered martensite and fresh martensite), the surface fraction of bainite and the surface fraction of bainite with low carbide content were quantified. After etching with NAOH-NaNO3 reagent, the surface fraction of fresh martensite was quantified.

[0169] Also, the surface fraction of ferrite was determined by optical and scanning electron microscopy, where the ferrite phase was identified after chemical polishing with a solution composed of hydrofluoric acid and hydrogen peroxide, and the non-recrystallized fraction was determined by scanning electron microscopy.

[0170] Additionally, the mechanical properties of the plates were determined.

[0171] The properties measured were hole expansion ratio HER, yield strength YS, tensile stress TS, uniform elongation UE and total elongation TE.

[0172] The yield strength YS, tensile strength TS, uniform elongation UE and total elongation TE were measured according to the ISO standard ISO6892-1 published in October 2009. The hole expansion ratio HER was measured according to the ISO16630:2009 standard.

[0173] Additionally, the difference in tensile strength, ΔTS, between the highest and lowest tensile strength areas of the plate was measured.

[0174] The microstructure of the steel plate and its mechanical properties are shown in Table III below.

[0175] [Table 3] TIFF0007650885000004.tif255170

[0176] In Table III, M is the surface fraction of martensite, FM is the surface fraction of fresh martensite, TM is the surface fraction of tempered martensite, B is the surface fraction of bainite, F is the surface fraction of ferrite, the column “UF<30%” indicates whether the surface fraction of non-recrystallized ferrite is less than 30%, and LBC / B is the fraction of bainite that is low carbide-containing bainite.

[0177] The composition of Steel 1 contains less than 0.4% Cr, resulting in insufficient hardenability, and the percentage of self-tempered martensite fraction does not reach 4%, while the ferrite fraction is higher than 50%. An even higher ferrite fraction is achieved in Example 1-a, which is annealed at a temperature lower than Ac3-20°C. As a result, the tensile strength does not reach 780 MPa and the hole expansion ratio does not reach 35% in Example 1-a.

[0178] The compositions of steels 2 and 3 also contain less than 0.4% Cr and more than 2.0% Mn. This high Mn content leads to too much stabilization of the austenite, so that too high a martensite fraction is formed during cooling from the annealing temperature and the bainite fraction is too low. As a result, the yield strength is too high. Also, this Mn content above 2.0% leads to a banded structure and the hole expansion ratio does not reach 35%.

[0179] The composition of steel 4 is according to the invention. Example 4-b is produced by the method according to the invention and has a structure according to the invention, and therefore reaches the targeted mechanical properties. Figure 2 shows the structure of this example 4-b. In this figure, M stands for martensite, CFB stands for carbide-free bainite and F stands for ferrite.

[0180] In contrast, Example 4-a is a 3-phase 3-phase 1-100% 10% 10% 15 ... H2 The structure does not contain sufficient self-tempered martensite, and the hole expansion ratio HER does not reach 35%.

[0181] The composition of steel 5 contains too much C and Mn and insufficient Ti and B. The composition of steel 6 contains too much C and Mn, insufficient Ti and B and too low Cr. As a result, examples 5-a, 5-b, 6-a and 6-b do not have the structure as claimed, in particular the ferrite fraction is too high (ferrite forms on cooling) and the bainite fraction is too low, leading to too high yield strength and hole expansion ratio not reaching 35%.

[0182] The composition of Steel 7 also contains too much C and Mn, too low a Cr content, and too high a Nb content. Example 7-a contains too much ferrite, too much non-recrystallized ferrite, and too low a bainite fraction, and does not reach the target yield strength and hole expansion ratio.

[0183] The composition of steel 8 is according to the invention. Examples 8-b, 8-g and 8-h are produced by the method according to the invention and have the structure according to the invention, and therefore reach the targeted mechanical properties.

[0184] In contrast, Example 8-a is annealed at a temperature TH2 lower than Ac3-20°C, and the structure does not contain enough self-tempered martensite, does not contain enough bainite, and contains too much ferrite, resulting in a hole expansion ratio HER of less than 35%.

[0185] Examples 8-c, 8-d and 8-e were coiled at too high a coiling temperature, resulting in a structure that does not contain enough martensite, does not contain enough self-tempered martensite, does not contain enough bainite and contains too much ferrite. As a result, the tensile strength does not reach 780 MPa. Also, the tensile strength is not uniform, with the difference in tensile strength ΔTS exceeding 7%.

[0186] Example 8-f shows that the annealing temperature T is too low. H2 When annealed at 100° C., the structure contained too little self-tempered martensite and the hole expansion ratio did not reach 35%.

[0187] In Example 8-i, the temperature was held too high after annealing, so that the fraction of self-tempered martensite became too high, the yield strength became higher than 550 MPa, and the hole expansion ratio did not reach 35%.

[0188] Example 8-j is a retention time t that is too short c As a result, the fraction of self-tempered martensite was too high due to incomplete transformation to bainite, resulting in a yield strength higher than 550 MPa and a hole expansion ratio not reaching 35%.

[0189] Example 8-k shows that the heating rate V is too fast to the annealing temperature. H’ The resulting structure contains more than 30% non-recrystallized ferrite, the hole expansion ratio does not reach 35%, and the yield strength is too high.

[0190] Since the composition of steel 9 contains too much Mo and example 9-m is annealed at too low an annealing temperature, the structure of the steel is not according to the invention and the targeted properties are not achieved.

[0191] The composition of Steel 10 contains too much C and not enough Cr, Nb and B. As a result, the martensite fraction is too high and the hole expansion ratio does not reach 35%. Figure 1 shows the structure of Example 10-a. In this figure, M indicates martensite, CFB indicates bainite without carbides, F indicates ferrite, and BC indicates bainite with carbides.

[0192] The composition of steel 11 is according to the present invention. Example 11-b is produced by the method according to the present invention and has a structure according to the present invention, and therefore achieves the targeted mechanical properties.

[0193] In contrast, Example 11-a is a 3-phase 3-phase 11-phase 11-phase 11-phase H2 annealed at 300°C, the structure does not contain enough self-tempered martensite, does not contain enough bainite, and contains too much ferrite. As a result, the hole expansion ratio HER does not reach 35%.

[0194] Example 11-c also has a temperature T lower than Ac3-20℃. H2 The steel was annealed at 1000 K and then coiled at a coiling temperature that was too high. The structure did not contain enough martensite or enough self-tempered martensite, but contained too much ferrite, and the tensile strength did not reach 780 MPa. The tensile strength was also not uniform, with the tensile strength difference ΔTS exceeding 7%.

[0195] The composition of steel 12 contains more than 0.085% C. As a result, the implementation of the method according to the invention does not achieve the targeted structure and therefore also the targeted properties. Example 12-c again shows that coiling at too high a coiling temperature leads to a tensile strength difference ΔTS of more than 7%.

[0196] The composition of steel 13 contains too much Mn and insufficient contents of Ti and B. As a result, the targeted structure and the targeted properties are not achieved by carrying out the method according to the invention. In particular, due to the insufficient contents of Ti and B, the martensite fraction does not reach 10% and the tensile strength is lower than 780 MPa.

Claims

1. A cold rolled annealed steel sheet having the following properties in weight percent: 0.060%≦C≦0.085% 1.8%≦Mn≦2.0% 0.4%≦Cr≦0.6% 0.1%≦Si≦0.5% 0.010%≦Nb≦0.025% 3.42N≦Ti≦0.035% 0≦Mo≦0.030% 0.020%≦Al≦0.060% 0.0012%≦B≦0.0030% S≦0.005% P≦0.050% 0.002%≦N≦0.007% The balance of the composition is iron and inevitable impurities resulting from refining, and the cold rolled annealed steel sheet has an area fraction of the following: - between 34 and 80% bainite, between 10 and 16% martensite, and - a microstructure consisting of between 10 and 50% ferrite, the area fraction of non-recrystallized ferrite relative to the total structure being less than 30%; The martensite is composed of self-tempered martensite and fresh martensite, and the area fraction of the self-tempered martensite is between 4% and 10% with respect to the entire structure.

2. The cold rolled and annealed steel sheet according to claim 1, wherein the composition includes 0.0005%≦Ca≦0.005%.

3. 3. The cold rolled annealed steel sheet according to claim 1 or 2, wherein the cold rolled annealed steel sheet is a temper rolled sheet having a tensile strength comprised between 780 MPa and 900 MPa, a yield strength YS comprised between 450 MPa and 550 MPa, a total elongation TE of at least 15%, and a hole expansion ratio HER of at least 35% measured according to ISO standard 16630:2009.

4. The cold rolled annealed steel sheet according to any one of claims 1 to 3, wherein the cold rolled annealed steel sheet has a thickness comprised between 0.7 mm and 2.3 mm.

5. 5. The cold rolled annealed steel sheet according to claim 4, wherein the cold rolled annealed steel sheet has a thickness of at least 2.0 mm.

6. The cold rolled annealed steel sheet according to any one of claims 1 to 5, having a length of at least 500 m in the rolling direction, and a difference in tensile strength between the highest tensile strength region and the lowest tensile strength region of the cold rolled annealed steel sheet is at most 7% of the tensile strength of the highest tensile strength region.

7. The cold-rolled annealed steel sheet according to any one of claims 1 to 6, wherein the cold-rolled annealed steel sheet comprises a coating of zinc or a zinc alloy obtained by continuous dip coating.

8. The cold-rolled annealed steel sheet according to any one of claims 1 to 6, wherein the cold-rolled annealed steel sheet comprises a coating of zinc or a zinc alloy obtained by vacuum deposition.

9. A method for producing a cold rolled annealed steel sheet, comprising the following successive steps: The following, in percent by weight: 0.060%≦C≦0.085% 1.8%≦Mn≦2.0% 0.4%≦Cr≦0.6% 0.1%≦Si≦0.5% 0.010%≦Nb≦0.025% 3.42N≦Ti≦0.035% 0≦Mo≦0.030% 0.020%≦Al≦0.060% 0.0012%≦B≦0.0030% S≦0.005% P≦0.050% 0.002%≦N≦0.007% providing a semi-finished product made of steel having a composition comprising: - subjecting the semi-finished product to a temperature T H1 Then, the heated semi-finished product is heated to Ar3 to T NR The final rolling temperature T FRT (Ar3 is the start temperature of the austenite transformation during cooling of the steel, T NR is the non-recrystallization temperature of said steel), obtaining a hot rolled steel sheet; - the hot-rolled steel sheet is cooled at a first cooling rate of at least 10 ° C / s to a coiling temperature T higher than the martensite finish temperature Mf of the steel and lower than 500 ° C. coil and the hot-rolled steel sheet is cooled to a coiling temperature T coil to obtain a structure consisting of bainite or consisting of bainite and martensite and / or pearlite, the area fraction of pearlite being less than 15%; - cold rolling the hot rolled steel sheet with a cold rolling reduction of at least 40% to obtain a cold rolled steel sheet; - The cold-rolled steel sheet is annealed at an annealing temperature T between Ac3-20 ° C. and Ac3 + 15 ° C. H2 reheating to the annealing temperature T H2 The average heating temperature V ranges from 1° C. / sec to 50° C. / sec. H and between 600° C. and Ac1, the average heating rate V is between 1° C. / s and 10° C. / s H’ and the cold-rolled steel sheet is reheated at the annealing temperature T H2 and an annealing time t of at least 30 seconds. H2 to obtain a structure containing at least 50% austenite; - cooling the cold-rolled steel sheet at a second cooling rate V comprised between 10 ° C. / s and 50 ° C. / s C2 Temperature T is between 440°C and 480°C. C cooling until The cold-rolled steel sheet is subjected to a holding time t comprised between 20 seconds and 500 seconds at a temperature comprised between 440 ° C. and 480 ° C. C holding for a period of - cooling said cold rolled steel sheet at a third cooling rate V C3 of at least 1 °C / s to ambient temperature; The cold rolled annealed steel sheet has an area fraction of: - between 34 and 80% bainite, between 10 and 16% martensite, and - a microstructure consisting of between 10 and 50% ferrite, the area fraction of non-recrystallized ferrite relative to the total structure being less than 30%; The martensite is composed of self-tempered martensite and fresh martensite, and the area fraction of the self-tempered martensite is between 4% and 10% with respect to the entire structure. method.

10. The method for producing a cold rolled annealed steel sheet according to claim 9, wherein the composition contains 0.0005%≦Ca≦0.005%.

11. The annealing time t H2 The method for producing a cold rolled annealed steel sheet according to claim 9 or 10, wherein the maximum heating time is 500 seconds.

12. The annealing temperature T H2 is included between Ac3 and Ac3+15° C., and the second cooling rate V C2 The method for producing a cold-rolled annealed steel sheet according to any one of claims 9 to 11, wherein the heating rate is between 10 ° C. / sec and 20 ° C. / sec.

13. The method for producing a cold-rolled annealed steel sheet according to any one of claims 9 to 12, wherein the cold-rolled steel sheet is hot-dip plated in a bath at a temperature of 480 ° C or less during the holding in the temperature range between 440 ° C and 480 ° C. The method for producing a cold-rolled annealed steel sheet according to any one of claims 9 to 12,

14. The method for producing cold rolled annealed steel sheet according to claim 13, wherein the cold rolled annealed steel sheet is coated with Zn or a Zn alloy.

15. The method for producing a cold rolled annealed steel sheet according to any one of claims 9 to 12, wherein after cooling to ambient temperature, a zinc or zinc alloy coating is applied by vacuum deposition.

16. The method for producing a cold-rolled annealed steel sheet according to any one of claims 9 to 15, wherein the cold rolling reduction is between 40% and 80%.

17. The method for producing a cold rolled annealed steel sheet according to any one of claims 9 to 16, wherein after cooling to ambient temperature, the steel sheet is temper rolled with a temper rolling reduction comprised between 0.1 and 0.4%.

Citation Information

Patent Citations

  • High-strength steel sheet having extremely reduced deterioration in aging property and having excellent baking hardenability, and method for producing the same

    JP2009249733A

  • High-strength steel sheet and high-strength hot-dip galvanized steel sheet having excellent workability, and method for producing them

    JP2010275627A

  • Precipitation strengthening type dual phase cold rolled steel sheet, and method for producing the same

    JP2010285657A

  • High-strength cold-rolled steel sheet excellent in uniform elongation in direction of 45 degrees with respect to rolling direction, and method for manufacturing the same

    JP2012021225A

  • High strength plated steel sheet for weld structure member and manufacturing method therefor

    JP2014189812A